Idiopathic Acute Exudative Polymorphous Vitelliform Maculopathy: Insight into Imaging Features and Outcomes - Sónia Torres-Costa; Susana Penas; Ângela Carneiro; Renato Santos-Silva; Rodolfo Moura; Elisete Brandão; Fernando Falcão-Reis; Luís Figueira (Case Reports in Ophthalmological Medicine, 2020)
The authors describe imagiological findings in idiopathic exudative polymorphous vitelliform maculopathy. A 41-year-old woman complained of bilateral blurry vision. Best-corrected visual acuity was 20/20 bilaterally. Bilateral small serous neurosensory detachments in the fovea were seen at fundoscopy and confirmed by spectral-domain optical coherence tomography. Fluorescein angiography was unremarkable. Indocyanine green angiography presented discrete hyperfluorescent spots on the posterior pole. Later, more bleb-like lesions with a vitelliform appearance and hyperautofluorescent on blue fundus autofluorescence were detected. One year later, a complete resolution of the fluid was observed. To conclude, multimodal evaluation of patients with idiopathic exudative polymorphous vitelliform maculopathy is essential for the correct diagnosis of this disease.